KUALITAS PELAYANAN BERBASIS TEKNOLOGI INFORMASI DI KANTOR BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN KABUPATEN GOWA - Juma, Syahrul; Mappamiring, Mappamiring; Adys, Abdul Kadir (Universitas Muhammadiyah Makassar, 2023)
The purpose of this study was to determine the quality of information technology-based services at the Customs Office for the Acquisition of Rights to Land and Buildings in Gowa Regency. employees in serving service users and employee expertise in carrying out the service process is implemented and runs well, namely ensuring that incoming reports are accurate and providing personnel who are experts in their respective fields according to information technology-based services, c) responsiveness of service users and perform these services quickly has been and is running well as evidenced by responding to every incoming report even though it is not during working hours and providing information and carrying out service procedures according to the set time, d) the guarantee has gone well. This is evidenced by the apparatus that provides services according to a predetermined time and remains in accordance with applicable procedures. d. Empathy has been running well, this is indicated by the availability of online complaints and aspirations facilities so that it is easy for the public to make complaints and complaints online.